Integration of Uptime Kuma Application Monitoring and MikroTik Router System using Prometheus and Grafana - Defani, Refalia; wijayanto, Danur (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
A network monitoring system plays a crucial role in ensuring service availability and optimizing network infrastructure performance. This study aims to integrate the Uptime Kuma application monitoring system and MikroTik router devices using Prometheus and Grafana at Life Media Company. The developed monitoring system is designed to provide real-time monitoring of services and network devices through a centralized dashboard that is more efficient and informative. The system was developed using the PPDIOO methodology, which includes the phases of Prepare, Plan, Design, Implement, Operate, and Optimize. The implementation results indicate that the integrated monitoring system offers significant improvements over the previous system in terms of access stability, monitoring visualization completeness, and the availability of more detailed technical information. The technical data successfully displayed include bandwidth usage, CPU load, memory usage, service latency, and service availability levels. The system also utilizes a 10-second scraping interval to collect data periodically, enabling faster identification of potential connectivity issues. This study contributes to the development of adaptive, open-source network monitoring systems by demonstrating that it can flexibly monitor various devices and services, while also being efficient—requiring no additional hardware and capable of displaying real-time technical data through a centralized dashboard without relying on commercial systems. In the future, the system can be further enhanced by implementing automated notifications and alerting features to strengthen its overall monitoring capabilities.